Identification and Characterization of a Novel Emaravirus Associated With Jujube (Ziziphus jujuba Mill.) Yellow Mottle Disease - Yang, Caixia; Zhang, Song; Han, Tong; Fu, Jingjing; Di Serio, Francesco; Cao, Mengji (Frontiers in Microbiology, 2019)
A previously unreported disease affecting jujube (Ziziphus jujuba Mill) trees was observed in China (Liaoning province) in 2015 and named jujube yellow mottle disease (JYMD), due to prevalent symptoms on the leaves. Diseased plants produced also malformed and discolored fruits. In an attempt to identify the possible causal agent of JYMD, high-throughput sequencing of small RNA libraries was performed and a novel virus, tentatively named jujube yellow mottle-associated emaravirus (JYMaV), identified and characterized. Six genomic RNA segments of JYMaV were completely sequenced. Each one contains a single open reading frame in the viral complementary strand and two untranslated regions with complementary 5’ and 3’ terminal ends, thus showing typical features of other negative-stranded RNA viruses. RNA1 (7.1 kb), RNA2 (2.2 kb) and RNA3 (1.2 kb) encode putative proteins that, based on their conserved motifs, have been identified as the RNA dependent RNA polymerase, the glycoprotein and the nucleocapsid proteins, respectively. These proteins share significant sequence identity (52.1-70,4%) with proteins encoded by raspberry leaf blotch emaravirus (RLBV). RNA4 (1.5 kb) and RNA5 (1.2 kb) code for two putative 30K movement proteins also related to the homologous RLBV protein. The functional role of the protein encoded by JYMaV RNA6 remains unknown. These data together with the phylogenetic relationships of JYMaV with other emaraviruses support the proposal that JYMaV is the representative member of a novel species in the genus Emaravirus In agreement with this proposal, virus-like particles and double-membrane-bound bodies similar to those previously reported for other emaraviruses were observed by transmission electron microscopy in extracts and tissues from symptomatic leaves, respectively. A specific RT-PCR-based detection method has been developed that was used in a preliminary field survey that provided results strongly supporting the close association of JYMaV with the novel disease.